Ecology of the brain: the phenomenology and biology of the embodied mind - Fuchs, Thomas (Oxford University Press, 2018)
Introduction -- Part 1. Criticism of neurobiological reductionism. Cosmos in the head? -- The brain as the subject's heir? -- Part 2. Body, person, and the brain. Foundations : subjectivity and life -- The brain as an organ of the living being -- The brain as an organ of the person -- The concept of dual aspectivity -- Implications for psychiatry and psychological medicine -- Conclusion